Comparison of Transpulmonary Thermodilution and Calibrated Pulse Contour Analysis with Pulmonary Artery Thermodilution Cardiac Output Measurements in Anesthetized Dogs - Garofalo, N. A.; Teixeira-Neto, F. J.; Rodrigues, J. C.; Cerejo, S. A.; Aguiar, A J A; Becerra-Velásquez, D. R. (Oxford University Press (OUP), 2016)
BACKGROUND: Transpulmonary thermodilution (TPTDCO ) and calibrated pulse contour analysis (PCACO ) are alternatives to pulmonary artery thermodilution cardiac output (PATDCO ) measurement. HYPOTHESIS: Ten mL of ice-cold thermal indicator (TI10 ) would improve the agreement and trending ability between TPTDCO and PATDCO compared to 5 mL of indicator (TI5 ) (Phase-1). The agreement and TA between PCACO and PATDCO would be poor during changes in systemic vascular resistance (SVR) (Phase-2). ANIMALS: Eight clinically normal dogs (20.8-31.5 kg). METHODS: Prospective, experimental study. Simultaneous TPTDCO and PATDCO (averaged from 3 repetitions) using TI5 and TI10 were obtained during isoflurane anesthesia combined or not with remifentanil or dobutamine (Phase-1). Triplicate PCACO and PATDCO measurements were recorded during phenylephrine-induced vasoconstriction and nitroprusside-induced vasodilation (Phase-2). RESULTS: Mean bias (limits of agreement: LOA) (L/min), percentage bias (PB), and percentage error (PE) were 0.62 (-0.11 to 1.35), 16%, and 19% for TI5 ; and 0.33 (-0.25 to 0.91), 9%, and 16% for TI10 . Mean bias (LOA), PB, and PE were 0.22 (-0.63 to 1.07), 6%, and 23% during phenylephrine; and 2.12 (0.70-3.55), 43%, and 29% during nitroprusside. Mean angular bias (radial LOA) values were 2° (-10° to 14°) and -1° (-9° to 6°) for TI5 and TI10 , respectively (Phase-1), and 38° (5°-71°) (Phase-2). CONCLUSIONS AND CLINICAL IMPORTANCE: Although TI10 slightly improves the agreement and trending ability between TPTDCO and PATDCO in comparison to TI5 , both volumes can be used for TPTDCO in replacement of PATDCO . Vasodilation worsens the agreement between PCACO and PATDCO . Because of PCACO 's poor agreement and trending ability with PATDCO during SVR changes, this method has limited clinical application.
Keywords: Indicator dilution cardiac output; Monitoring; Pulse contour analysis